Cultural factors and sexual practices of women living with HIV / AIDS in South West, Nigeria. - Akinbebije, Christianah Olufunbi; Anumaka, Blessing Ijeoma; Dahiru, Abba (Advances in Social Sciences Research Journal, 2020)
The study examined the cultural factors and sexual practices of women living with HIV/AIDS in South West, Nigeria. Three states were chosen out of the six states in South West. One hundred and Eighty Three women living with HIV/AIDS were drawn from the three states. Descriptive survey research design was used for the study. A questionnaire titled “Questionnaire on women living with HIV/AIDS (QWLH/A)” was administered on the respondents. The findings revealed that there is high significant relationship between cultural factor and sexual practices in placing women on the risk of contracting HIV/AIDS. Based on the findings, it was recommended that government should introduce sex education for young Nigerians. The practice of widow inheritance can die slowly by testing both parties involved before the inheritance is carried out.